The Real Estate Transfer Tax and Government Ideology: Evidence from the German States - Manuela Krause; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2017)
In 2006, the reform of the German fiscal constitution realigned legislative powers between the federal and the state governments. Since 2007, the German state governments have been allowed to design real estate transfer tax rates. We investigate whether government ideology predicts the levels and increases in the real estate transfer tax rates; and show that leftwing and center governments were more active in increasing the real estate transfer tax rates than rightwing governments. The result is important because many voters were disenchanted with the policies and platforms of the established German parties in the course of the euro and refugee crisis. Disenchantment notwithstanding, the established political parties are still prepared to offer polarized policies.
Keywords: D72; H20; H71; P16; R38; 330; taxation; real estate transfer tax; reform; partisan politics; government ideology; German states